Women in the tradition of male-female power relations in the post-divorce period: A case study in Tanjung Village, Sumenep Regency, Madura - Sinta Nuriyah; Maurelia Vidiara Auliaviav; Nahdia Arifani (Masyarakat, Kebudayaan dan Politik, 2021)
Power relations between women and men tend to benefit men more than women. In this context, power has the meaning of influencing other parties and making them unconscious. This study aimed to determine the relationship between men and women in terms of power relations. Power is not a function of class domination based on economic control or manipulation of ideology (Marx), and it is also not based on other people’s charm. Instead of perceived negatively, power should be regarded as something positive and productive. This study employs Foucault’s theory of power relations, and Foucault illustrates that power is not centralized and unstructured. Power has the meaning of complex situations and strategies in people’s lives. This study used a qualitative method with interview, observation, and documentation techniques. Men’s power relations in Sumenep Regency to their former spouses occurred in the form of responsibility and attention, giving even the formal husband and wife relationship has ended. Power relations can be seen from verbal communication. According to Foucault, knowledge is not a theory; however, discourse is a truth built by initiators. Men continue to dominate their former spouses when they visited their ex-wife and still fulfill the responsibilities of children living costs. The situation will lead to a reluctance’s sense to the ex-wives because of the effort to maintain a good relationship. The ex-wife chose to ask permission from the ex-husband when to remarry as a tradition to avoid misunderstanding in previously-related parties.